2018
DOI: 10.3390/app8112149
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Use of Recycled Concrete Aggregates Originating from a Single Ready-Mix Concrete Plant

Abstract: The waste produced from ready-mixed concrete (RMC) industries poses an environmental challenge regarding recycling. Three different waste products form RMC plants were investigated for use as recycled aggregates in construction applications. Crushed hardened concrete from test specimens of at least 40 MPa compressive strength (HR) and crushed hardened concrete from returned concrete (CR) were tested for their suitability as concrete aggregates and then used as fine and coarse aggregate in new concrete mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Results from the isothermal conduction calorimetry test demonstrate that the cement sludge no longer has any hydration properties, even after reactivation with pozzolanic material; similar results were obtained by Anastasiou et al [30].…”
Section: Cement Sludgesupporting
confidence: 83%
See 1 more Smart Citation
“…Results from the isothermal conduction calorimetry test demonstrate that the cement sludge no longer has any hydration properties, even after reactivation with pozzolanic material; similar results were obtained by Anastasiou et al [30].…”
Section: Cement Sludgesupporting
confidence: 83%
“…As far as the cement sludge is concerned, Anastasiou et al [30] evaluated the feasibility of using this component for the production of mortars with a cement replacement rate of 10% and 20% and as an additive for soil stabilization. The results showed that mortars made with dried and crushed cement slurry (d = 75 µm), as a partial substitute for cement (10% replacement), showed a compressive strength comparable to that of the mortar totally produced with Portland cement.…”
Section: Introductionmentioning
confidence: 99%
“…The study focuses on providing geotechnical solutions to expansive soils using blended CDW for base and subbase stabilization. The main objective of this study was to review the physico mechanical and chemical properties of CDW in order to benchmark compressive strength of natural aggregates [27][28][29][30]. The review looks into the use of CDW as a means of sustainability to the environment and to encourage use of quality materials in civil engineering, combined to improve strength and stiffness and reduced swell potentials of expansive soils.…”
Section: Methodsmentioning
confidence: 99%
“…An investigation on the use of recycled concrete aggregates originating from a single ready-mix concrete plant was performed by Anastasiou et al [7]. Crushed hardened concrete from test specimens (HR) and from returned concrete (CR) were tested for their suitability as concrete aggregates, and cement sludge fines (CSF) originating from the washing of concrete trucks were tested as filler.…”
Section: Large-scale Applications Of Recycled Aggregate Concretementioning
confidence: 99%